Effective Local Government Organizational Structure in Improving the Quality of Public Services: A Literature Study - Sudrajat, Ade; Mustiraya, Rd. Raya; Framesthi, Dyah Bayu (Asosiasi Ahli Administrasi Indonesia, 2025)
This research examines the relationship between the effectiveness of local government organizational structure and the improvement of public service quality through a comparative analysis of two main studies, namely Effendi (2022) and Soeardi (2019). The discussion focuses on three main aspects: structural dimensions of the organization, management and implementation factors, and the impact of organizational change on service effectiveness. The results show that organizational restructuring oriented towards simplifying structures, decentralizing authority, and adjusting functional roles can improve the efficiency and responsiveness of public services. The success of these changes is largely determined by the application of strategic management and Total Quality Management (TQM) principles, as well as adaptive and participatory leadership. The study also confirms the importance of matching the design of the organizational structure with the local context, in line with the principles in various regulations such as Law No. 23 of 2014, Law No. 5 of 2014, and national bureaucratic reform policies. Thus, public sector organizational restructuring needs to be designed as a holistic process that synergizes structural design, managerial strategies, and human resource management to produce more effective, efficient, and accountable public services.